Chronic circadian advance shifts abolish melatonin secretion for days in rats - Xu, Gang (Neurobiol Sleep Circadian Rhythms, 2018)
Melatonin deficiency has been proposed to underlie higher risks for cardiovascular and several other diseases in humans experiencing prolonged shiftwork. However, melatonin secretion has not been monitored longitudinally during consecutive shifts of the light:dark (LD) cycles in the same individuals (animals or humans) and the extent of melatonin deficiency is unknown in individuals experiencing consecutive LD shifts. We investigated the effect of consecutive LD shifts on melatonin secretion in adult F344 rats using continuous online pineal-microdialysis. The rats were entrained to the 12 h:12 h LD cycle before the shifts. The LD cycle was then advanced (n=5) or delayed (n=4) for six hours every four days for four consecutive times. The rats exhibited marked asymmetry in response to delay or advance LD shifts. While rats exposed to the repeated LD delay shifts always exhibited melatonin secretion throughout the entire periods, repeated LD advance shifts suppressed nocturnal melatonin secretion for several consecutive days in the middle of the 3-week period. Moreover, melatonin offset after LD delay and melatonin onset after LD advance determined the rate of circadian pacemaker reentrainment. Additionally, melatonin offset was phase locked at the new dark/light junctions for days following LD advance. These data demonstrate that chronic LD shifts are deleterious to melatonin rhythms, and that this effect is much more pronounced during advance shifts. These data may enhance our understanding of impact of LD shifts on our circadian timing system and benefit better design of shiftwork schedules to avoid melatonin disruption.